Pembuatan Konten pada Media Sosial Instagram sebagai Strategi Kreatif dalam Pengembangan UMKM - Rizky Oktarina Costa; Roomilda Roomilda (Universitas Pahlawan Tuanku Tambusai, 2022)
During the Covid-19 pandemic, UMKM experienced a decline in sales and turnover. Based on the results of the LIPI survey, it was found that UMKM who sold online on social media were far more able to survive. The difficulties experienced by UMKM are in the form of content ideas that will be created and posted. Instagram social media requires interaction between users, but if the content presented is not interesting then there will be no interaction which will lead to no trust in UMKM that offer their products. The aim of this activity is that UMKM can create content to increase sales. At the beginning, the MSME material was introduced to the target market. This is important to know so that the content created is right on target. The next stage is to get content ideas that are needed by the target market. The next session explains the scope of Instagram. Then also conveyed how to communicate tips on social media. This activity was successfully carried out and yielded positive results, seeing the enthusiasm of the participants in participating in the activity and also based on the results of the questionnaire that was filled out by the participants at the end of the activity.